A comparative study of penalty rate imposed on exemption of affordable housing development through affordable housing policy implementation at state level in Malaysia / Nurul Azreen Syamira Azlan - Azlan, Nurul Azreen Syamira (2023)
As provided in the National Affordable Housing Policy, the State Government can implement a penalty or levy on the developers that are given an exemption from developing affordable housing in Malaysia. However, the implementation of these penalties in West Malaysia is not uniform, as states have their own interpretations and policies based on national policies. Through literature reviews, only seven states have implemented this penalty or levy, including Perak, Kelantan, Terengganu, Kedah, Pahang, Melaka, and Johor. The aim of the research is to objectives of this research are to identify the similarities and dissimilarities of penalty or levy implementation and evaluate the effects of penalty or levy implementation at the state level. The research is qualitative research and the method used for data collection is a structured interview session with the representatives from the housing department of each state and a literature review on related topics. For sampling, the researcher has divided all the states that implement the penalty or levy into three different categories for the purpose of this research which are the fixed percentage, range of percentages, and fixed value. The chosen states for this research are Perak, Kelantan and Terengganu. Content analysis will be used to analyse the data collection in each state.